Grounding the Quran Through the Thousand Hafiz Movement in Muslim-Majority Countries - Sindy Wahyuni; Mudhiyatul Huda; Yufrizal Yufrizal; Mutathahirin Mutathahirin; Ikhwan Rahman (International Islamic Studies Development and Research Center (IISDRC), 2025)
Learning and memorizing the Quran is a demanding process that requires patience, time, and effective pedagogical strategies. Many students experience fatigue, boredom, and discouragement during this journey, which calls for innovative approaches to sustain motivation and strengthen memorization quality. This study aims to analyze the effectiveness of the Waqf 1,000 Hafiz Program in enhancing Quranic memorization among students in Islamic educational institutions. A qualitative case study design was employed, with data collected from 100 informants consisting of teachers and students, selected through purposive sampling. The primary instrument was an in-depth interview guide, supported by audio recordings and field notes. Data were analyzed thematically using Miles and Huberman’s interactive model, including data reduction, display, and conclusion drawing. The findings reveal that the implementation of the Waqf 1,000 Hafiz Program significantly improves students’ memorization achievements, discipline, and spiritual motivation. Moreover, the program strengthens the institution’s role in shaping religious character and fostering commitment to Quranic values. The implications highlight the importance of replicating similar initiatives in Muslim-majority countries as a strategy for grounding the Quran in daily life, while also serving as a scholarly reference for Islamic education and waqf-based policy development.